Using AquaCrop as a Decision-Support Tool for Small-Scale Irrigation Systems Was Dictated by the Institutional and Market Incentives in Ethiopia - Biazin, Birhanu; Wondatir, Solomon; Tilahun, Gebeyaw; Asaro, Nuredin; Amede, Tilahun (Frontiers in Water, 2021)
The threat of water scarcity in sub-Saharan Africa is exacerbated by the expanding agricultural water needs, increasing climate variability and inappropriate land use. It calls for technological and institutional innovations to improve water productivity, while sustaining the resources base. This study was undertaken to examine the effect of deficit and supplementary irrigation for staggered production of potato driven by market opportunities at different periods in northeastern Ethiopia. We used potato (Solanum tuberosum) to demonstrate AQUACrop as a tool for improving water productivity during Belg (short) and Meher (long) rainfall seasons. A field experiment was undertaken using supplementary irrigation at different levels of potato crop water satisfaction (50% ETc, 75% ETc, 100% ETc and rainfed conditions) during the Belg (February-May 2020) and Meher (July-October 2020) seasons. Upon proper calibration of AquaCrop for the local potato variety (Belete), long-term simulations revealed that the mean net irrigation requirements were 249mm during Belg season while the probability of applying supplementary irrigation during Meher was less than 10% when the effective precipitation was greater than the crop water requirement (ETc) in more than 75% of the years. Although there was significantly higher potato tuber yield from the 100% ETc than that from the 75% ETc, the latter had higher water supply efficiency than the former. Long-term simulations further revealed that the number of rainfall days was more important than the amount of rainfall during the growing period. We engaged water users’ associations to employ the recommendation and enforce supplementary irrigation as predicted by the model and we present farmers’ response and reasons for resistance towards water saving approaches. Hence, we concluded that 50%ETc and 75%ETc irrigation levels can still be recommended upon proper scheduling to address long dry spells, especially during the middle growth stages in the face of irrigation conflict. However, the institutional settings and market incentives associated with it are the major drivers of adopting improved irrigation water management practices.